The investigation of Indian and central Asian swords through neutron methods. (August 2018) - Grazzi, Francesco; Cantini, Francesco; Salvemini, Floriana; Scherillo, Antonella; Schillinger, Burkhard; Kaestner, Anders; Edge, David; Williams, Alan
Abstract: In this work we present the analysis of the micro-structural features of ancient Indian blades carried out by neutron tomography and neutron diffraction. The results provide a clear identification of the different types of steel used to produce such weapons. Among them, only a small proportion of the large number of swords produced in India were made of hypereutectoid patterned steel, namely wootz, also (misleadingly) known as "Damascus steel". The results permitted us to determine the spatial distribution of the iron and steel components inside the swords and the size and orientation of the microstructure of the ferrite and cementite grains in the wootz steel. These results are an important step forward towards the comprehension of the metal preparation and the forging procedure to produce swords made of wootz steel. These results are further proof of the validity of the use of neutron techniques as a non-destructive scientific analytical tool for quantitative authentication and characterization of ancient metal artefacts. Graphical abstract: In this work we present the analysis of the micro-structural features of ancient Indian blades carried out by neutron tomography and neutron diffraction. The results provide a clear identification of the different types of steel used to produce such weapons. Unlabelled Image Highlights: The morphological and microstructural features of wootz steel were analyzed. Analysis was performed by using non-destructive neutron methods: neutron imaging and neutron diffraction. Specific microstructural features in steel were identified as anisotropy in cementite and its specific spatial distribution.